Biogenically synthesized gold nanocarrier ameliorated antiproliferative and apoptotic efficacy of doxorubicin against lung cancer - Albulaihed, Yazeed; Mishra, Prakriti; Saeed, Mohd; Alabdallah, Nadiyah M.; Ginawi, Tarig; Ansari, Irfan Ahmad (Frontiers in Pharmacology, 2024)
Conventional chemotherapy treatment is commonly linked to significant side effects due to high therapeutic doses. In this regard, nanoformulations with chemotherapeutic medications hold promise in enhancing drug effectiveness through the reduction of therapeutic dosages, thereby mitigating the potential for adverse side effects. Because of numerous applications in the biomedical arena, there has been a rising interest in developing an environmentally acceptable, long-lasting, and affordable technique for the production of gold nanoparticles. In this particular context, the incorporation of plant extracts in the production of metallic nanoparticles has garnered the interest of numerous scholars. Here, we report the synthesis of gold particles by the green method using Cannabis sativa L. leaf extract and their conjugation with doxorubicin. The biogenic synthesis of gold nanoparticles was ascertained through an absorption peak at a wavelength of 524 nm, and it was shifted to 527 nm when conjugated with doxorubicin.Nanoparticles were found to be stable exhibiting a zeta potential value of -20.1 mV, and it changed to -12.7 mV when loaded with doxorubicin. The hydrodynamic diameter of nanoparticles was determined to be 45.64 nm and it was increased to 58.95 nm when conjugated with the drug. The average size of nanoparticles analyzed by TEM was found to be approximately 17.2 nm, while it was 23.5 nm in the case of drug-nanoconjugate. Moreover, there was a significant amelioration in the antiproliferative potential of doxorubicin against lung cancer A549 cells when delivered with gold nanocarrier, which was evident by the lower IC50 and IC75 values of drug-nanoconjugates in comparison to drug alone. Furthermore, the inhibitory effect of drug-nanoconjugates and drug alone was characterized by alteration in the cell morphology, nuclear condensation, increased production of reactive oxygen species, abrogation of mitochondrial membrane potential, and enhanced caspase activities in A549 cells.In sum, our results suggested enhanced efficacy of doxorubicin-gold nanoconjugates, indicating effective delivery of doxorubicin inside the cell by gold nanoparticles.